CSR as a Corporate Communication Strategy: An Analysis of Public Perception - Deni Saputra, Muhammad; Hanutama, Paundra (Jurnal sosial dan sains, 2025)
Corporate Social Responsibility (CSR) has become a fundamental element in corporate communication strategies, shaping corporate reputation, brand perception, and stakeholder engagement. As consumer awareness of social and environmental issues increases, companies are compelled to integrate CSR into their strategic communication efforts. However, public skepticism toward CSR initiatives remains a challenge, particularly when CSR communication lacks transparency, authenticity, and stakeholder involvement. This study investigates how CSR functions as a corporate communication strategy and analyzes public perception of CSR initiatives, addressing the key research question: How does CSR communication influence stakeholder trust, engagement, and corporate reputation? While prior research has explored CSR communication, limited studies have systematically examined the intersection of CSR strategies, digital transformation, and public perception in a rapidly evolving corporate environment. This paper contributes to the literature by evaluating CSR communication through stakeholder-oriented frameworks, digital engagement strategies, and participatory communication models, offering a comprehensive and updated perspective on CSR effectiveness in corporate communication. This study employs a Systematic Literature Review (SLR) methodology to synthesize existing research on CSR communication, stakeholder perception, and brand reputation. Data were collected from peer-reviewed journal articles, conference proceedings, and industry reports using academic databases such as Scopus, Web of Science, and Google Scholar. The analysis was conducted using NVivo for qualitative coding and VOSviewer for bibliometric mapping, allowing for a structured and in-depth exploration of key themes and trends in CSR communication. Findings indicate that CSR communication is most effective when it is transparent, participatory, and aligned with corporate values. The study highlights the importance of storytelling, digital platforms, and two-way stakeholder engagement in enhancing CSR credibility. Additionally, the results reveal that companies integrating CSR within their core business strategies and maintaining long-term commitment experience greater consumer trust, higher engagement levels, and improved corporate legitimacy. This study concludes that CSR as a corporate communication strategy must be strategically integrated, evidence-based, and stakeholder-driven to foster trust, loyalty, and positive public perception. Companies that engage in co-creation of CSR initiatives, leverage digital communication tools, and prioritize transparency are more likely to achieve sustainable stakeholder relationships and long-term business success. The implications suggest that businesses must continuously refine their CSR communication strategies to remain credible and relevant in a socially conscious marketplace